Contextualizing Priestly Roles in the Formative Years of Jerusalem's Second Temple - Ganzel, Ṭovah (Biblica, 2023)
The Persian-era Judean Temple compound included a self-administered community of functionaries, and its priests demonstrated departures from those that were described in the earlier Temple. Babylonian temples in the Persian period, I suggest, offer us a meaningful context in which to situate some of the unique features of these priests, among other officials as described in Ezra-Nehemiah. The roles of the priests during the formative period of the Jerusalem Temple saw an evolution that may have been informed by priestly roles in the Persian Empire.